A Madras Motor Neuron Disease Patient With Cerebellar Atrophy: A New Clinical Feature - Long, Ling; Cai, Xiaodong; Liu, Jia; Kang, Zhuang; Li, Jing; Huang, Zizhen; Guo, Ruomi; Zou, Yan; Lu, Zhengqi (Frontiers in Neuroscience, 2018)
A 34-year-old Chinese Han female complaining of general muscle weakness and wasting for 9 years. She was admitted for aggravation of her symptoms caused by respiratory distress. She also suffered from bulbar palsy. She had no hearing loss, visual problems, or cerebellar signs. Her parents had a consanguineous marriage, though there was no family history of these symptoms. Pure tone audiometric findings demonstrated no definite abnormality. Electromyography demonstrated neurogenic damage. Brain magnetic resonance imaging revealed cerebellar atrophy, dominantly in anterior lobe. Gene sequencing of whole gene exomes was negative. She was finally diagnosed with Madras motor neuron disease (MMND), a rare subtype of motor neuron disease. No definite therapy was available for MMND, and she died of respiratory tract infection 1 year later. Previous studies have shown that cerebellar signs are positive in 17.2% patients of MMND, but no case with cerebellar atrophy has been reported before. Thus, here we describe cerebellar atrophy as a new clinical feature of MMND